The Effect of Nephelium lappaceum Fruit Flesh on Growth Dynamics for Catla catla Fish (Labeo catla, Hamilton 1822) Fingerlings - Madhina , V.; Ravichandran , R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Globally, aquaculture is one of the fastest-growing industries. Feeding management of fish plays an important role in the efficient and successful culture of fish and provides essential nutrients for the optimum growth of fish, which leads to success in commercial aquaculture. There is a need for enhanced feed efficiency and growth performance in cultured freshwater fish species. The aim of the present study was to evaluate the effects of Nephelium lappaceum fruit feed supplementation on the growth performance of Catla fish, Studies were continued, for 60 days. The observations made on Nephelium lappaceum fruit (1, 2, and 3 percentage of feed) supplementation of experimental fish showed significantly increased body weight, length, weight gain, and SGR, while FCR was significantly decreased compared with the control diet. The higher SGR values suggest its growth potential, and the lower value of FCR indicates the high efficiency of the experimental culture fish. The study suggests that the Nephelium lappaceum fruit diet, which is more effective, promotes Catla catla fish growth and can be used as an alternative to commercial feed for Catla catla fingerlings.